Genetic causes of sudden cardiac death in the young. (May 2017) - Mazzanti, Andrea; Maragna, Riccardo; Priori, Silvia G.
Abstract : Purpose of review: In this article, we discuss the most recent and relevant studies published in the field of inherited arrhythmogenic disorders, focusing in particular on channelopathies (Long QT syndrome, Brugada syndrome, and catecholaminergic polymorphic ventricular tachycardia) and arrhythmogenic right ventricular cardiomyopathy (ARVC). Recent findings: We discuss the updated diagnostic criteria for channelopathies released by the European Society of Cardiology, the new results on the value of programmed electrical stimulation in patients with Brugada syndrome, and the recent evidences supporting a genotype-specific therapy for Long QT syndrome type 3. Moreover, we will present further insights into the clinical course and risk stratification of patients affected by ARVC, analyzing in particular the role of antiarrhythmic drugs for the prevention of life-threatening arrhythmias. Finally, we will explore the innovative therapeutic approaches that may be available in the future for patients with inherited arrhythmogenic disorders, such as the gene therapy. Summary: The review will aid physicians in their clinical work when managing patients with inherited arrhythmias and ARVC, providing the most recent information for diagnosis, risk stratification, and management. Abstract : Supplemental Digital Content is available in the text